2016
DOI: 10.1093/mnras/stw3134
|View full text |Cite
|
Sign up to set email alerts
|

Probing the accretion disc structure by the twin kHz QPOs and spins of neutron stars in LMXBs

Abstract: We analyze the relation between the emission radii of twin kilohertz quasi-periodic oscillations (kHz QPOs) and the co-rotation radii of the 12 neutron star low mass X-ray binaries (NS-LMXBs) which are simultaneously detected with the twin kHz QPOs and NS spins. We find that the average co-rotation radius of these sources is r co ∼ 32 km, and all the emission positions of twin kHz QPOs lie inside the corotation radii, indicating that the twin kHz QPOs are formed in the spin-up process. It is noticed that the u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 78 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…It is noticed that NS is in the spin-up state when R m < R co (or ν K > ν s ), while it is in the spin-down state when R m > R co (or ν K < ν s ). To explore the magnetosphere-disk structures of NS-LMXBs and kHz QPOs, Wang et al (2017Wang et al ( , 2020 investigated the link of the twin kHz QPOs with NS spin-up state. Moreover, the authors also showed that the magnetosphere-disk radii of HB/NB in Z sources cluster around the range of ∼20-29 km/∼16-20 km, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…It is noticed that NS is in the spin-up state when R m < R co (or ν K > ν s ), while it is in the spin-down state when R m > R co (or ν K < ν s ). To explore the magnetosphere-disk structures of NS-LMXBs and kHz QPOs, Wang et al (2017Wang et al ( , 2020 investigated the link of the twin kHz QPOs with NS spin-up state. Moreover, the authors also showed that the magnetosphere-disk radii of HB/NB in Z sources cluster around the range of ∼20-29 km/∼16-20 km, respectively.…”
Section: Introductionmentioning
confidence: 99%